(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, Khoja Muhammad Porso’s thoughts on the sacred words used in the Khojagan-Naqshbandiya order are analyzed philosophically. The noble goals of encouraging man to protect himself from himself and to be compassionate by forming a high respect for his species are highlighted.